1980
DOI: 10.1159/000119889
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty in Children

Abstract: In children, acquired skull defects often close spontaneously. This is most likely to take place when the dura mater and the pericranium are intact. Congenital skull defects rarely close spontaneously. Cranioplasty will be needed when a bone defect has failed to close or when it is unlikely to do so. Various methods are available: autogenous bone, acrylic resin, and metal prostheses have been widely used. A series of 68 operations performed on children under the age of 15 years is reviewed. It is concluded tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…2,4,6,8,9,14 Five of these studies included only patients who had had decompressive craniectomy, while the study by Blair et al…”
Section: Methods Of Storagementioning
confidence: 99%
See 3 more Smart Citations
“…2,4,6,8,9,14 Five of these studies included only patients who had had decompressive craniectomy, while the study by Blair et al…”
Section: Methods Of Storagementioning
confidence: 99%
“…2,6,8,9 For the remaining 2 studies, Piedra et al reported 4 infections in 61 patients, and Bowers et al reported 9 infections in 54 patients. 4,14 A comparison of the 6 studies that involved using frozen bone with the 1 study that involved using bone stored at room temperature, as above, suggests that frozen bone storage yields a lower risk of infection (OR 0.32, 95% CI 0.08-1.30, p = 0.103).…”
Section: Methods Of Storagementioning
confidence: 99%
See 2 more Smart Citations
“…11,17,29,127 In a recent retrospective analysis by Williams et ) with no noted complications after 1 year of follow-up. 128 Radiographic attenuation caused by metallic cranioplasty can create imaging artifacts with CT scans and radiographs.…”
Section: 101mentioning
confidence: 98%